cho a,b,c khác nhau đôi một và 1/a+1/b+1/c==0 . Rút gọn biểu thức P=a^2/a^2+2bc+b^2/b^2+2ac+c^2/c^2+2ab

Question

cho a,b,c khác nhau đôi một và 1/a+1/b+1/c==0 . Rút gọn biểu thức
P=a^2/a^2+2bc+b^2/b^2+2ac+c^2/c^2+2ab

in progress 0
Bella 2 tuần 2021-11-24T09:46:40+00:00 1 Answers 6 views 0

Answers ( )

    0
    2021-11-24T09:48:30+00:00

    Đáp án: $P=1$

    Giải thích các bước giải:

    Ta có:

    $\dfrac{1}{a}+\dfrac{1}{b}+\dfrac1c=0$

    $\to bc+ca+ab=0$

    $\to bc=-ab-ac$

    $\to 2bc=bc-ab-ac$

    $\to a^2+2bc=a^2+bc-ab-ac$

    $\to a^2+2bc=(a^2-ab)+(bc-ac)$

    $\to a^2+2bc=a(a-b)-c(a-b)$

    $\to a^2+2bc=(a-b)(a-c)$

    $\to\dfrac{a^2}{a^2+2bc}=\dfrac{a^2}{(a-b)(a-c)}$

    Tương tự

    $\dfrac{b^2}{b^2+2ca}=\dfrac{b^2}{(b-c)(b-a)}$

    $\dfrac{c^2}{c^2+2ab}=\dfrac{c^2}{(c-a)(c-b)}$

     $\to P=\dfrac{a^2}{(a-b)(a-c)}+\dfrac{b^2}{(b-c)(b-a)}+\dfrac{c^2}{(c-a)(c-b)}$

     $\to -P=\dfrac{a^2}{(a-b)(c-a)}+\dfrac{b^2}{(a-b)(b-c)}+\dfrac{c^2}{(b-c)(c-a)}$

     $\to -P=\dfrac{a^2(b-c)+b^2(c-a)+c^2(a-b)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{a^2(b-c)+b^2c-b^2a+c^2a-c^2b}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{a^2(b-c)+(b^2c-c^2b)-(b^2a-c^2a)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{a^2(b-c)+bc(b-c)-a(b^2-c^2)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{a^2(b-c)+bc(b-c)-a(b-c)(b+c)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{(b-c)(a^2+bc-a(b+c))}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{(b-c)(a^2+bc-ab-ca)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{(b-c)((a^2-ab)+(bc-ca)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{(b-c)(a(a-b)-c(a-b)}{(a-b)(b-c)(c-a)}$

     $\to -P=\dfrac{(b-c)(a-c)(a-b)}{(a-b)(b-c)(c-a)}$

    $\to -P=-1$

    $\to P=1$

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )